Pengembangan E-Modul Tipe Flipbook Berbasis Studi Kasus Stunting untuk Meningkatkan Penguasaan Konsep pada Materi Sistem Pencernaan - Windy Oktaviani; Margaretha Solang; Masra Latjompoh (Jurnal Penelitian Pendidikan IPA, 2023)
The study aims to describe the validity, practicality and determine the effectiveness of flipbook-type e-modules based on stunting case studies to improve the concept mastery on digestive system material. This research uses research and development methods modified. Data collection techniques using observation sheets, questionnaires and tests. The trial was conducted on 37 students of Class XI IPA 2 SMA Negeri 1 Kabila. The research results found: (1) validity tests is in â€œVery Goodâ€ category based on the percentage of content/material validation of 87.50% and construction validation of 98.00% (2) practicality test is in "Very Good" category based on the percentage of learning implementation of 92.63%, student activity of 90.22%, teachers responded of 96.00%, and students response of 98.96% (3) effectiveness test based on the results of small group N-Gain score analysis worth of 0.70 (Effective). Based on the results of the research, it can be concluded that the flipbook-type e-module based on stunting case studies to improve concept mastery on digestive system material meets the valid, practical and effective criteria so that it is suitable for use in Biology learning to improves students concept mastery on digestive system material at SMA Negeri 1 Kabila